Chemical analysis for explosive compounds in water, sediment, and flatfish Limanda limanda (dab) collected from shipwrecks in the North Sea to assess the biological effects of old World War munitions - Lillian Tabea Hannah Bünning; Romy Brüning; Lars Christian Scheer; Romina Marietta Schuster; Ute Marx; Matthias Brenner; Edmund Maser (PANGAEA, 2026)
This dataset documents field investigations on release of legacy World War I munition explosive compounds into the surrounding marine environment, with a focus on shipwreck sites in the North Sea. Three historically well-documented wrecks were selected: the light cruisers SMS Mainz and SMS Ariadne, and the minelayer submarine UC30. These wrecks were chosen based on detailed archival information regarding their sinking circumstances and cargo, their unambiguous identification, and their accessibility for scientific diving operations. As a munition-free control, a reference area outside known wreck fields was sampled (Naturschutzgebiet Borkum Riffgrund). The flatfish Limanda limanda (dab) was selected as a sentinel species. Sampling was conducted during several cruises with the research vessel Heincke (HE 573, April 2021 – SMS Mainz; HE 596, April 2022 – UC30 and SMS Ariadne; HE 607, September 2022 – UC30; HE 613, February 2023 – SMS Ariadne) and with the Uthörn (May 2022 – reference site). Water was sampled with a CTD rosette water sampler at different depths and processed on board by solid phase extraction at 4 °C. Sediment was sampled with a Van Veen grab sampler and frozen at -20 °C. Fish were caught using bottom trawls deployed as close as possible to the wreck structures. Captured fish were transferred to seawater tanks prior to dissection. Each specimen was measured, weighed, and assessed biometrically to calculate condition factors as indicators of general health. Tissue samples were immediately frozen in liquid nitrogen and stored at -20 °C. Samples were processed in the lab according to established protocols. All samples were analyzed by gas chromatography triple quadrupole mass spectrometry (GC-MS/MS) for the explosive TNT and its metabolites 2- and 4-ADNT.